Análise de sensibilidade das propriedades mecânicas e geométricas no fenômeno brake squeal e no desgaste de freios a disco de motocicleta - Miranda, Matheus Henrique Pires (2021)
One of the factors of influence on driver comfort is undoubtedly the noise. The noise generated by the brakes, in addition to causing discomfort, can cause uncertainty as to the existence of mechanical failure in the brake system. Among the types of noise related to disc brakes, what has been generating a greater interest of researchers is Squeal noise. This thesis is concerned with the disc brake squeal problem for motorcycles, as well as the wear of brake pads. The aim of the present thesis is developing a finite element model of the motorcycle disc brake in order to improve the understanding of the influence of material and operational parameters on squeal and wear generation. Archard’s Wear modelling and Stability analysis of the disc brake assembly is accomplished to find unstable frequencies. A parametric study is carried out to investigate the effect of changing mechanical properties of the disc, back plate, friction material and geometric parameters, such as disc and pad thicknesses, on squeal generation. The results of simulation indicated that material and geometric parameters play a substantial role in generating the squeal noise. On the other hand, wear is most affected by operating conditions and pad material properties.